THE ROLE OF RELIGIOUS SPIRITUAL VALUES IN YOUTH EDUCATION (World Bulletin of Social Sciences, 2026)
The article discusses the role and importance of religious values in the spiritual development of people. It discusses the essence of religious values, such as humanism, morality, spiritual purification, and social order. It discusses the content of values in the Holy Quran and hadiths. It discusses issues of values in social life. It discusses the importance of Islamic values in shaping the spiritual worldview of young people